Extradural Thoracic Arachnoid Cyst En-Bloc Resection and Follow-Up: A Case Report - Seddighi, Afsoun; Nikouei, Amir; Sedighi, Amirsaeed; Asadpour, Mohammad; Masoudian, Noushin; Samaei, Afshin (International Clinical Neuroscience Journal, 2017)
Background: Arachnoid cysts are cerebrospinal fluid (CSF) fluid-filled sacs that are located between the brain and spinal cord. Spinal column arachnoid cysts are rare and mostly asymptomatic, being mostly located in intradural regions. We reported a patient who presented with neurological deficits and mid-thoracic extradural arachnoid cyst treated with en-bloc resection. Case Presentation: Patient was a 34-year-old female who presented with progressive back pain, lower extremity weakness and paresthesia in her lower limbs. Magnetic resonance imaging (MRI) study revealed an extradural hyperintense signal lesion in T2-weighted, extending from T7 to T9, which did not enhance on T1-weighted post-contrast MRI. Patient underwent T6-T10 laminectomy and en-bloc resection of the lesion which was compatible with arachnoid cyst after histopathological examination. Patient did not experience worsening of neurological symptoms and lesion recurrence in clinical and imaging evaluation during 2-year follow-up. Conclusion: Clinical and neuroimaging evaluation of every patient with progressive neurological deficits should be carried out in detail. This report suggests that rare spinal lesion, as extradural spinal arachnoid cyst in this case, may cause neurologic deficits and en-bloc resection of the lesion is feasible and may prevent local recurrence.